Determination of yarn length in warp beams for sizing - Fettahov, Resul; Cihangirova, Mahire; Yeşil, Yalçin (Ege Universitesi mailto:teksek@mail.ege.edu.tr, 2016)
There has been a vast amount of attempts in the weaving companies for reducing the production costs without compromising the product quality. One of the most common methods is the reduction of yarn waste produced during weaving. In this study, theoretical investigations were carried out for determination of the yarn length wound beams, prepared in sizing and warp transfer processes, for reducing the yarn wastes. In addition, equations which determine the length of yarn to be wound on separate beams of different types of creels in sizing machines have been developed and proposed for practical use. © 2017 Elsevier B.V., All rights reserved.
Keywords: Sizing Process; Warp Beam; Weaving; Yarn Length; Yarn Wastes